Ancient Catalogues of Memory Institutions in Manuscript Collections of the Wróblewski Library of Lithuanian Academy of Sciences: the Inventory of the Slutsk St. Elias Monastery - Cicėnienė, Rima (Bibliotheca Lituana, 2012)
Ancient book lists and catalogues are one of the most important sources of cultural and scientific history. Books listed in the documents allow us to research the history of not only various institutions and their libraries, but also the history of literature and science, the totality of writing functioned in the country at the time, as well as human and institutional cultural connections. This article has two objectives: firstly – to briefly discuss the old book lists and catalogues stored in the manuscript collections of the Wroblewski Library of Lithuanian Academy of Sciences (hereinafter – WLLAS); secondly – to publish the inventory of the Slutsk St. Elias Monastery in 1575. Manuscripts in the WLLAS funds were analyzed in order to attain these purposes. The article approach reasons to compile catalogues, information capture techniques and their changes using particular documents from Library funds. The conclusion of this publication reveals that if all in the library remaining ancient book lists/catalogues and the information contained in them were studied and systematized, a new and sizable artifact complex for the scientists would form. This would allow the continuation of already commencing works and the broadening of aspects in the studies of the library history and the ancient books collections’ composition along with changes in it. This is particularly important for studying the functioning of books or library history in their earliest periods in GDL. This paper presents the publication of the inventory from Slutsk St. Elias Monastery in 1575. This document illustrates the way books were listed at that time, providing additional knowledge about the earliest known institutional collections of books in GDL. A large St. Elijah‘s Monastery’s book collection of the relevant time period, also included in this article, strengthens the argument, that Slutsk was one of the biggest Lithuanian Grand Duchy’s written language centers in the 16th century. Extensive amount of information on historical icons, liturgical objects, variety of textiles used in the time period might appeal to anthropologists, interested in ecclesiastical art, historians of Orthodox Church researching the evolution of rites, liturgical utensils used and church architecture, finally, linguists, examining the Ruthenian language and terminology of the time.
Keywords: none